The Principle of Common Good in Ibuanyidanda Philosophy and Egocentrism in Nigeria’s Political Leadership - Onyemachi Felix Chukwudi (Universitas Negeri Makassar, 2021)
The paper aims at resolving the issue of egocentrism using the principle of common good in Ibuanyidanda Philosophy within the context of Nigeria’s political leadership. The paper makes analyses of the concepts of egocentrism, leadership, common Good and Ibuanyidanda Philosophy. The paper examines egocentrism in Nigeria’s political leadership, and identifies it as a menace which among other ravages, has consequences of economic, social and moral decline in the nation. The paper argues that Nigeria would have known growth and development in all spheres of her existence if the leaders had conscientiously given comprehensive and selfless services in their leadership mandates. The paper, therefore, concludes that Nigeria will only experience all-round development and attain an enviable height in the comity of nations when the Principle of Common Good in Ibuanyidanda Philosophy which promotes inclusiveness, committedness and selflessness as against self-centredness, exclusiveness and ‘we-them’ mentality is adopted by policy makers, and ingrained in Nigeria’s political leadership.